Seneca and the satire of Emperor Claudius - Almeida, José Carlos Silva de (Argumentos - Revista de Filosofia, 2014)
This article presents a masterpiece of Roman satire written by Lucius Annaeus Seneca, in which the Emperor Claudius, instead of becoming a god after his death, is transformed into a “pumpkin”, image of a fool, who in life had been the object of laughter for his physical and moral defects in the Roman court and among the subjects.